Leadership tasks in public health: findings from the National Board of Public Health Examiners’ job task analysis - Dubois, Cerina; Dissen, Anthony; Bowen, Michael; Kurz, Rick; Foster, Allison; Buys, David (Frontiers in Public Health, 2025)
IntroductionPublic health leadership plays a crucial role in shaping effective health policies and practices. The National Board of Public Health Examiners (NBPHE) conducts a job task analysis (JTA) survey every 5–7 years to update the Certified in Public Health (CPH) examination. The objective of this study is to examine the JTA findings on leadership tasks in public health practice.MethodsIn April 2022, through the collaboration of expert panels and a validation survey, 103 tasks organized into ten domains were established for the JTA survey. The JTA survey was distributed online to current public health professionals. Across the tasks in the ten domains, respondents were asked about frequency (Scale of 1–6; how often they performed this task) and criticality (Scale of 1–5; how important this task was to their job).ResultsA total of 2,091 public health professionals responded to at least 82 of the 103 tasks (80%) and were included in the analysis. Approximately 86% of respondents worked in the United States and 41% had earned their CPH credential. Average frequency ratings ranged from 2.38 to 5.58, indicating that task ratings ranged from being performed never performed, every few years to daily. Average criticality ratings ranged from 2.46 to 4.64, indicating that task ratings ranged from not important to critically important. Specific to leadership, it was found that the ‘leadership’ domain ranked 2nd highest for both frequency and criticality.ConclusionOur findings suggest that leadership-focused development as part of academic public health programs and continuing education for the workforce is essential. Future research may examine how individuals perform on the leadership domain of the CPH exam across multiple characteristics to better inform additional workforce development strategies.